Ecosystem-based interventions and farm household welfare in degraded areas: Comparative evidence from Ethiopia. (June 2017) - Getnet, Kindie; Mekuria, Wolde; Langan, Simon; Rivington, Mike; Novo, Paula; Black, Helaina
Abstract: Agricultural productivity and farm household welfare in areas of severe land degradation can be improved through ecosystem-based interventions. Decisions on the possible types of practices and investments can be informed using evidence of potential benefits. Using farm household data together with a farm level stochastic simulation model provides an initial quantification of farm income and nutrition outcomes that can be generated over a five year period from manure and compost based organic amendment of crop lands. Simulated results show positive income and nutrition impacts. Mean farm income increases by 13% over the planning period, from US32, 833 under the business as usual situation (application of 50 kg DAP and 25 kg urea ha − 1 yr − 1 ) to US37, 172 under application of 10 t ha − 1 yr − 1 farm yard manure during the first three years and 5 t ha − 1 yr − 1 during the last two years. As a result of organic soil amendment, there is an associated increase in the available calorie, protein, fat, calcium, and iron per adult equivalent, giving the improvement in farm household nutrition. The evidence is substantive enough to suggest the promotion and adoption at scale, in degraded ecosystems, of low cost organic soil amendment practices to improve agricultural productivity and subsequent changes in farm household welfare. Highlights: Ecosystem-based interventions provide a mechanism to improve farm household welfare. Farm income and nutrition improve as a result of organic soil amendment. The initial evidence generatedis encouraging. It can provide guidance to promote practice adoption and out-scaling. Cash flow and farm income can be sensitive to technology cost.